P-OGC77 Why curative treatment rates are so low for stage I/II Oesophago-gastric cancer in the West of Scotland? – A five year review. (16th December 2021) - Khan, Khurram; Gall, Lewis; Miller, Gillian; Macdonald, Andrew; Craig, Carol; MacKay, Colin; Forshaw, Matthew
Abstract: Background: Over the last decade, quality performance indicators (QPIs) have been used to drive improvements in cancer care in Scotland.  QPI-11 targets curative treatment rates for oesophago-gastric (OG) cancer and this target has been consistently missed.  This study aimed to investigate why patients with potentially curable Stage I and II OG cancer did not receive curative treatment.  Methods: The West of Scotland MCN database was interrogated for patients with newly diagnosed stage I and II OG cancer between January 2015 and December 2019 to identify those patients who did not have curative treatment.  Electronic records were then analyzed and the reason for the non curative treatment recorded. Results: 260 patients (mean age 78.3 ± 9 years; 114 (43.8%) female) were identified. Median Scottish Index of Multiple Deprivation was 4 (IQR 2-7).   There were 159 (61.2%) oesophageal cancers, 196 (75.4%) adenocarcinomas and 174 (66.9%) were Stage II cancers.  Formal CPEX fitness was assessed in only 20 patients (7.7%).  Reasons for curative treatment not being received were as follows: not clinically fit (n = 216 (83.1%)); patient declined curative treatment (n = 17 (6.5%)); disease progression (n = 16 (6.2%)) and identification of synchronous cancers (n = 9 (3.5%)). Conclusions: Lack of fitness for radical treatment is the predominant reason for Stage I and II OG cancer patients in the West of Scotland not being treated with curative intent.  This may be related to the previously described "West of Scotland" effect on health comorbidities.